Cost‐effectiveness of a carcinoembryonic antigen (CEA) based follow‐up programme for colorectal cancer (the CEA Watch trial). (March 2016) - Verberne, C. J.; Wiggers, T.; Grossmann, I.; de Bock, G. H.; Vermeulen, K. M.
Abstract: Aim: The study CEA Watch (Netherlands Trial Register 2182) has shown that an intensified follow‐up schedule with more frequent carcinoembryonic antigen (CEA) measurements but fewer outpatient visits detects more curable recurrences compared with the usual follow‐up protocol in colorectal cancer (CRC) patients. The aim of the study was to compare the cost and cost‐effectiveness between various follow‐up programmes. Method: In total, 3223 patients with stage I–III CRC were followed between October 2010 and October 2012. Direct medical costs were calculated per patient adding the costs for all visits, CEA measurements and imaging. Productivity losses and travel expenses were calculated using answers from questionnaires. The cost‐effectiveness displayed the additional costs per additional patient with recurrent disease and used an incremental cost‐effectiveness ratio (ICER) to compare them. Results: The mean yearly cost per patient was €548 in the intensified protocol and €497 in the control protocol. The ICER was €94 (95% CI €76–€157) per cent; to detect one additional patient with a recurrence in the intervention protocol compared with the control protocol would require an additional €9400. For curable recurrences, the ICER was €607 (95% CI €5695–€5728). Annual patient‐reported costs were €509 per year in the intervention protocol and €488 in the control protocol. Conclusion: The current study demonstrates that the direct medical and patient‐reported cost of a newly introduced, safe and effective way of CRC follow‐up was comparable to that of standard care. The ICER per curable recurrence was considered acceptably low.